GENERATION Z DIGITAL WALLET USERS: COMPLIANCE ANALYSIS IN THE PERSPECTIVE OF FIQH MU'AMALAH IN THE ERA OF FINANCIAL TECHNOLOGY - Puspita Handayani; Hawwa Zahrani; Eka Ayu Pratiwi; M. Rizal Yulianto (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This article aims to analyze the use of digital wallets by Generation Z from the perspective of sharia compliance in the perspective of fiqh mu'amalah in the era of financial technology. Method: The method used is a literature study with a normative-analytical approach to the concept of contract, prohibition of usury, gharar, and maisir, as well as the maqasid al-shari'ah approach. Results: The use of digital wallets is allowed as long as it meets the principle of contract clarity, is free from elements of riba and gharar, and is oriented towards benefits. However, structural challenges related to fund management, promotion transparency, and digital ethics require strengthening sharia governance. Novelty: This article contributes theoretically to contemporary mu'amalah fiqh studies and offers practical insights for developing fintech in alignment with Islamic values.